A Click Ligation Based on SuFEx for the Metal‐Free Synthesis of Sugar and Iminosugar Clusters. Issue 30 (15th August 2016) - Zelli, Renaud; Tommasone, Stefano; Dumy, Pascal; Marra, Alberto; Dondoni, Alessandro
Abstract : Although the preparation of anomeric glycosylsulfonyl fluoride was unsuccessful, a tetra‐ O ‐acetylated C ‐glucosylpropanesulfonyl fluoride was synthesized starting from the corresponding thioacetate via sulfonate formation as the key intermediate. This sulfonyl fluoride was a bench‐stable product that reacted promptly with primary and secondary alkylamines at 80 °C to give the corresponding sulfonamides in good yield. On the other hand, the same fluoride was inert toward arylamines whereas its precursor, the sulfonyl chloride, showed good reactivity. Another limitation of the acetylated sugar sulfonyl fluoride was its lack of reactivity with a multivalent aminated calixarene, this being due to acetyl transfer from the carbohydrate moiety to the amino groups of the scaffold. Fortunately, the tetra‐ O ‐benzylated C ‐glucosylpropanesulfonyl fluoride, prepared by the same reaction sequence employed for the synthesis of the acetylated analogue, reacted with the tetra‐aminopropyl‐calix[4]arene to afford the corresponding sulfonamide‐linked sugar cluster in high isolated yield. A similar approach to the synthesis of calixarene‐based iminosugar clusters was unsuccessful because 1‐deoxynojirimycin sulfonyl fluoride derivatives could not be generated. However, a tetra‐propylsulfonyl fluoride calixarene, obtained from the free‐OH calix[4]arene through a three‐step reaction sequence, underwent clean coupling with both C ‐glucosylpropylamine and N ‐aminopentyl‐1‐deoxy‐deoxynojirimycin derivatives to give the corresponding tetravalent sugar and iminosugar clusters. This metal‐free click reaction may constitute a valuable tool in the arsenal of ligation tools for the synthesis of multivalent carbohydrate architectures. Abstract : The metal‐free coupling between a tetra‐aminated calixarene and a bench‐stable C‐glycosylsulfonyl fluoride gave the corresponding sugar cluster in good yield. The reversed sulfonamide bioisostere of the latter was prepared using a tetrasulfonyl fluoride calixarene and a C‐glycosylalkylamine.